A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia) - Karanovic, Ivana (Zootaxa, 2018)
The Australian Candonidae ostracod fauna has few surface water representatives, despite Australia being one of the principal centers of Candonidae biodiversity. The majority of Australian species live in subterranean waters, with most genera and one tribe being endemic to the continent. Species in Australia show Tethyan and Gondwana connections, with relatives living in European and Central/South American subterranean waters. I describe Hancockcandonopsis gen. nov. from boreholes in the alluvial aquifers of the Peel River and Hunter Valley, which at present contains five species, of which three are named, H. inachos sp. nov., H. io sp. nov., and H. tamworthi sp. nov., and two are left on the open nomenclature. All species are allopatric and short range endemics. The genus belongs to the almost cosmopolitan Candonopsini tribe, and the major generic autapomorphy is a hook-shaped h3-seta on the cleaning leg. Characters on the prehensile palps and hemipenis of Hancockcandonopsis indicate a close relationship with the Queensland genus Pioneercandonopsis Karanovic, 2005 and two West Indies genera, Cubacandona Danielopol, 1978 and Caribecandona Broodbaker, 1983. A cladistic analysis, based on 32 Candonopsini species and 24 morphological characters, is used to test phylogenetic relationships among Candonopsini genera globally. Several hypotheses about the historical biogeography of this tribe are discussed.